IT strategy and management - Dubey, Sanjiva (PHI Learning, 2011)
"The book gives an in-depth study of the information technology as a strategic resource, the need for a strategic approach for its management, and the necessity of its alignment with business strategy. It explains how to prepare an effective plan for the implementation of information strategy. The book also describes how to evaluate the impact of IT on organizations and their workforce, and how to measure returns on IT investment. It also covers recent developments in IT management such as ITIL (Information Technology Infrastructure Library), IT service management, MOF (Microsoft Operations Framework), COBIT, and standards such as ISO 20000 and B527001, which are currently being practised by the industry but need more dissemination in the academic arena." -- Publisher's website.